Shield Agent as A Middleman Agent to Increase Brand Awareness of BPJS Employment and The Number of Participants Who Are Not Wage Earners (BPU) - Melly Aprianti; Erlita Ridanasti (Eduvest - Journal of Universal Studies, 2025)
The social security system is designed to provide social protection, ensuring that every individual can meet basic, decent living needs. However, in 2022, BPJS Ketenagakerjaan covered less than 50% of the workforce in Indonesia. BPJS Ketenagakerjaan launched the PERISAI Program to reach potential participants in hard-to-access areas. This research aims to analyze the marketing strategies and efforts of BPJS in increasing and maintaining membership in the Non-Wage Recipients (BPU) segment through the application of the STP marketing strategy, the 7P Marketing Mix, Brand Awareness, and the role of PERISAI Agents. The method used is descriptive qualitative data analysis, utilizing interviews with key informants to gather direct data. The study results show that the "PERISAI" strategy has proven to be quite effective in increasing BPU membership, as evidenced by its success in acquisition and more interactive and intensive communication with participants. Additionally, it was found that BPJS Ketenagakerjaan still needs to focus more on improving brand awareness, as some Non-Wage Recipients (BPU) are not sufficiently familiar with BPJS Ketenagakerjaan.